Empire of the Summer Moon : Quanah Parker and the Rise and Fall of the Comanches, the Most Powerful Indian Tribe in American History /: Quanah Parker and the Rise and Fall of the Comanches, the Most Powerful Indian Tribe in American History. (2011) - Gwynne, S.C
No abstract available